Interactive Spinal Cord Atlas - Susan Gagliardi; Charlene Baron; Sam Gorstein (Association of American Medical Colleges, 2009)
Abstract Introduction The Interactive Spinal Cord Atlas is one of a series of electronic atlases that we use in Mind, Brain and Behavior 1, the first-year Neuroscience course at the University of Massachusetts Medical School. Methods This atlas contains 11 transverse sections of the myelin-stained human spinal cord. Each section has been labeled with interactive drawings and questions that direct students to key information such as why it is important, or model the integration of neuroanatomic structure and functions with clinical applications. Learners can choose what teacher-generated atlas material to display, quiz themselves on it and get immediate feedback, turn on or off the teacher's comments, add their own annotations and drawings to the atlas images, and easily share their work electronically with other students or with the faculty. The atlas can be used as a supplement to lectures and/or small-group conferences in an introductory neuroscience course. It is intended to provide a framework for student-driven learning, and to help students integrate complex basic and clinical information about nervous system structure and function. Results Student evaluations of the atlases in the three years that they have been deployed have been extremely positive. In the spring 2006 class, 95% of students (n = 100) gave the interactive atlases the highest possible rating as helpful learning tools. All students reported studying the instructor-generated comments, 51% added a significant number of their own comments and drawings to the atlases, and 28% used the atlases collaboratively. Eighty-five percent of students gave the atlases the highest rating as a resource that helped them connect and integrate basic with clinical information. The teacher-generated interactive drawings and questions provide guidance in integrating information, but at the same time the format and design encourage each individual student to customize his or her atlas by adding drawings, notes or links to meet personal learning needs. Discussion Students are likely to find the atlas most helpful after they have acquired a core of knowledge about the spinal cord through lectures, discussions, or reading.